Hypersensitivity of Arabidopsis TAXIMIN1 overexpression lines to light stress is correlated with decreased sinapoyl malate abundance and countered by the antibiotic cefotaxime - Colling, Janine (Plant Signal Behav, 2016)
Peptide signaling in plants is involved in regulating development,(1,2) ensuring cross pollination through initiation of self-incompatibility(4) and assisting with recognition of beneficial (nitrogen fixing bacteria(5)) or unfavorable organisms (pathogens(6) or herbivores(7)). Peptides function to help plants to respond to a changing environment and improve their chances of survival. Constitutive expression of the gene encoding a novel cysteine rich peptide TAXIMIN1 (TAX1) resulted in fusion of lateral organs and in abnormal fruit morphology. TAX1 signaling functions independently from transcription factors known to play a role in this process such as LATERAL ORGAN FUSION1 (LOF1). Here, we report that the TAX1 promoter is not induced by the LOF1 transcription factor and that the TAX1 peptide neither interferes with transcriptional activation by LOF1.1 or transcriptional repression by LOF1.2. Furthermore, we found that TAX1 overexpressing lines were hypersensitive to continuous light, which may be reflected by a decreased accumulation of the UV-B protecting compound sinapoyl-malate. Finally, adding the antibiotic cefotaxime to the medium surprisingly countered the light hypersensitivity phenotype of TAX1 overexpressing seedlings.